CDK4: A Novel Therapeutic Target for Extramammary Paget’s Disease - Hashimoto, Hiroki; Kaku-Ito, Yumiko; Oda, Yoshinao; Ito, Takamichi (Frontiers in Oncology, 2021)
Background: The outcome of extramammary Paget’s disease (EMPD) is poor when it progresses to metastasis because of the lack of effective systemic therapies. Recently, CDK4-targeted therapy has attracted attention as a potential therapeutic target for some cancers. The aim of this study was to analyze the impact of CDK4 expression on the survival of patients with EMPD. Methods: We retrospectively reviewed 110 patients with EMPD. We conducted immunohistochemical analysis of CDK4 and cyclin D1 expression, and assessed the association between their expression and survival. Results: Most EMPD lesions (108/110, 98.2%) were positive for CDK4 staining and there was a positive correlation between CDK4 expression and cyclin D1 expression (r = 0.54, p < 0.001). Tumor thickness (p = 0.0003) and the presence of regional lymph node metastasis (p = 0.015) were significantly associated with high CDK4 expression. Regarding invasive EMPD, the multivariate analysis did not show the correlation between the expression of CDK4/cyclin D1 and survival outcomes (HR: 3.14, p = 0.14). Conclusion: The overexpression of CDK4 was identified as a major risk factor for disease progression. CDK4-targeted therapy could thus be a novel treatment option for unresectable EMPD.